Graph Representation: Comparative Study and Performance Evaluation - Arman, Nabil (My University, 2006)
In this study, a comparison is conducted among three major representations of directed graphs to illustrate major advantages and disadvantages of each representation scheme....
Keywords: Graph Representation, Path Matrix Representation